2008
DOI: 10.2169/internalmedicine.47.0930
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Challenge Test Does not Predict Gestational Diabetes Mellitus

Abstract: Objective It is widely acknowledged that identification and treatment of gestational diabetes mellitus (GDM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…A recent study conducted by V Mohan, et al in India showed a very low sensitivity of non-fasting GCT when compared to the IADPSG criteria (sensitivity 22.6%, specificity 97.8%) (21). Other studies done in South Asian ethnicity as well as in Caucasians too have revealed poor sensitivity of 50g and 75g GCT (19,22,23).…”
Section: Discussionmentioning
confidence: 96%
“…A recent study conducted by V Mohan, et al in India showed a very low sensitivity of non-fasting GCT when compared to the IADPSG criteria (sensitivity 22.6%, specificity 97.8%) (21). Other studies done in South Asian ethnicity as well as in Caucasians too have revealed poor sensitivity of 50g and 75g GCT (19,22,23).…”
Section: Discussionmentioning
confidence: 96%
“…This means that as many as 20% of patients undergoing GCT remain undiagnosed [24,25]. GCT has been criticized as poorly repeatable, unpleasant, impractical to perform, relatively expensive and time-consuming [26], with low specificity [27].…”
Section: Methods Of Screening and Diagnosingmentioning
confidence: 99%
“…To znači da će 20% pacijenta podvrgutih GCT ostati nedijagnostifikovan, čak i u slučaju primene univerzalnog skrininga 31 . Pored toga, GCT je slabo reproducibilan, neprijatan, nepraktičan za izvođenje, relativno skup i vremenski zahtevan 32 , sa visokom varijabilnošću i niskom specifičnošću 33 . Ipak, najveći broj profesionalnih udruženja veruje da je GCT najadekvatniji metod skrininga GdM-a 34,35,36 .…”
Section: Metode Skrininga šEćerne Bolesti Trudnicaunclassified